Feasibility of Collecting Multiple Patient-Reported Outcome Measures Alongside the Dutch Arthroplasty Register. (August 2020) - Tilbury, Claire; Leichtenberg, Claudia S; Kaptein, Bart L; Koster, Lennard A; Verdegaal, Suzan H M; Onstenk, Ron; der Zwaag, Henrike M J van der Linden-van; Krips, Rover; Kaptijn, Herman H; Vehmeijer, Stephan B W; Marijnissen, Willem-Jan C M; Meesters, Jorit J L; et al.
Background: Compliance rates with patient-reported outcome measures (PROMs) collected alongside arthroplasty registries vary in the literature. We described the feasibility of a routinely collected set PROMs alongside the Dutch Arthroplasty Register. Methods: The longitudinal Leiden Orthopaedics Outcomes of OsteoArthritis Study is a multicenter (7 hospitals), observational study including patients undergoing total hip or total knee arthroplasty (THA or TKA). A set of PROMs: Short Form-12, EuroQol 5 Dimensions, Hip/Knee injury and Osteoarthritis Outcome Score, Oxford Hip/Knee Score was collected preoperatively and at 6, 12, 24 months, and every 2 years thereafter. Participation rates and response rates were recorded. Results: Between June 2012 and December 2014, 1796 THA and 1636 TKA patients were invited, of whom 1043 THA (58%; mean age 68 years [standard deviation, SD: 10]) and 970 TKA patients (59%; mean age 71 years [SD 9.5]) participated in the study. At 6 months, 35 THA/38 TKA patients were lost to follow-up. Response rates were 90% for THA (898/1000) and 89% for TKA (827/932) participants. At 1 and 2 years, 8 and 18 THA and 17 and 11 TKA patients were lost to follow-up, respectively. The response rates among those eligible were 87% (866/992) and 84% (812/972) for THA and 84% (771/917) and 83% (756/906) for TKA patients, respectively. The 2-year questionnaire was completed by 78.5% of the included THA patients and by 77.9% of the included TKA patients. Conclusions: About 60% of patients undergoing THA or TKA complete PROMs preoperatively, with more than 80% returning follow-up PROMs. To increase the participation rates, more efforts concerning the initial recruitment of patients are needed.